Associations between maternal mental health, child dental anxiety, and oral health of 6- to 12-year-olds in Nigeria - Abiola Adetokunbo ADENIYI; Morenike Oluwatoyin FOLAYAN; Nneka Maureen CHUKWUMAH; Elizabeth Obhioneh OZIEGBE; Maha EL TANTAWI (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Maternal mental health affects their children's oral health. This study assessed the associations between maternal mental health and dental anxiety level, dental caries experience, oral hygiene, and gingival status among 6- to 12-year-old children in Nigeria. This was a cross-sectional study that recruited mother-child dyad participants through a household survey conducted in Ile-Ife, Nigeria. Data collected included the independent (maternal mental health risk, depressive symptoms, and child's dental anxiety), and dependent (caries experience, oral hygiene status, and gingival health status) variables. Multivariate logistic regression analysis was conducted to determine the associations between dependent and independent variables after adjusting for confounders (mothers' age, child's age, sex, and socioeconomic status). Statistical significance was set at p < 0.05. Of the 1411 mothers recruited, 1248 (88.4%) had low mental health risk, and 896 (63.5%) had mild depressive symptoms. As for the children, 53 (3.8%) had caries, 745 (52.8%) had moderate to high dental anxiety, 953 (63.0%) had gingivitis and 36 (2.6%) had poor oral hygiene. The maternal mental health risk was not significantly associated with the child's caries experience (AOR: 1.012; 95%CI: 0.860-1.190; p = 0.886), poor oral hygiene (AOR:1.037; 95%CI: 0.975-1.104; p=0.250), and moderate/severe gingivitis (AOR:0.887; 95%CI: 0.764-1.030; p = 0.115). Maternal depression status was not significantly associated with the child's caries experience (AOR: 0.910; 95%CI: 0.802-1.033; p = 0.145), poor oral hygiene (AOR: 1.016; 95%CI: 0.976-1.057; p = 0.439), and moderate/severe gingivitis (AOR: 0.963; 95%CI: 0.861-1.077; p = 0.509). Maternal mental health risk and depression do not seem to be risk factors for schoolchildren's oral health in Nigeria. Further studies are needed to understand these findings.